Analisis dalam Kasus Penyalahgunaan Deepfake dari Segi Perlindungan Data Pribadi dalam UU ITE dan UU PDP di Indonesia - Karo Karo, Rizky; Jiddan, Zein; Buono, Hanan Atanto (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
The rapid advancement of digital technology, particularly Deepfake technology, presents a serious challenge to the protection of privacy rights in Indonesia. This technology enables the realistic manipulation of an individual’s image and voice, potentially leading to crimes, defamation, and gross privacy violations. However, Indonesian positive law currently lacks specific regulations explicitly addressing the misuse of Deepfake technology. This study aims to examine the nature of privacy rights protection in Indonesia and analyze the existing legal protection against Deepfake misuse. The research utilizes a normative legal methodology with statutory, conceptual, and case approaches. The findings indicate that the right to privacy is a constitutional and human right recognized under Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Furthermore, privacy is considered a universal human right, acknowledged in the 1948 Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). Currently, legal protection against the misuse of Deepfake technology remains limited and relies heavily on the interpretation of the Information and Electronic Transactions Law (UU ITE) and the Criminal Code (KUHP). Therefore, the study concludes that it is necessary to establish new legal norms that explicitly regulate the misuse of Deepfake technology to provide maximal protection for the privacy rights of citizens.